Identification of Injuries in Amateur Boxing Athletes in Gorontalo City: Study for Developing Prevention and Treatment Strategies - Suleman, Ibrahim; Duhe, Edy Dharma Putra; B. Pomalango, Zulkifli; Ibrahim, Nurhaliza (PT Inovasi Pratama Internasional, 2024)
Injuries in boxing athletes often occur in the upper extremities of the body, especially the head and face, which can result in concussions, cuts and bruises. This research aims to identify the types of injuries experienced by boxing athletes in Gorontalo City and explore their causes. The method applied is a survey using questionnaires as the main data collection technique. The population of this study consisted of 50 active female boxing athletes from Gorontalo City. The results showed that the most common injuries occurring in boxing were injuries to the head and face (44%), followed by injuries to the wrist (29%), shoulders (29%), knuckles (22%), knees (16%), and ankle (16%). The main factors causing injury include conditions during training or competition (36%) and the time of injury (32%). Based on the results of this research, it can be concluded that the parts of the body most frequently injured are the head and face with a percentage of 44%. These findings emphasize the importance of developing injury prevention and treatment strategies, especially to the head and face, to improve the safety and health of amateur boxing athletes in Gorontalo.